Inflation and economic growth in LDCs - Walter Hamm (Intereconomics, 1973)
Economists find it difficult to reach agreement about the effects on economic growth of depreciation of the money value. One reason is that they define certain terms in different ways, another one is that many other factors as well as inflation have an impact on economic growth. They may intensify or compensate for positive and negative relations between inflation and economic growth.
Keywords: 330; Development Policy